Perbaikan Proses Complain Website Qoo10.co.id Menggunakan Usability Testing dan Compatibility Behavioural - Galih Prakoso; Hanifah Muslimah Az-Zahra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of e-commerce which is quite famous and is based in Korea is Qoo10.co.id, which has a percentage kujungan 28.70% according to alexa.com. In the case of the website Qoo10.co.id is the consumers who order goods by the number two when the goods come only one item is received, consumers do complain in the website there is no response from the party's website. Based on the issue be conducted research business process improvement in the website Qoo10.co.id based on e-commerce business process another decent enough in addressing the problems of implementation and complain complain using the form. The study will describe BPMN from 3 websites that made a comparison that is the website Bukalapak, Blibli, and Zalora. Behaviour compatibility comparison of BPMN is used for each to get compliance behaviour. Usability testing is used to get the value of the efficiency, effectiveness and satisfication, to get the value of effectiveness and efficiency will be done with a task scenario for satisfication questionnaire will use SUS which would filled 6 respondents. From the results of the calculation of any comparison website has a compatible behaviour and the value of the effectiveness and efficiency of each comparison website is 100%, a value Bukalapak, Blibli 70,83 satisfication 72,083, Zalora 66,25. calculation Of behaviour compatibility and usability will be done of making BPMN and the user interface for the website Qoo10.co.id, in the calculation of the BPMN has a behaviour which is compatible and to value the effectiveness and efficiency of the obtained value is 100%, while for values satisfication is 79.167.